Machine learning techniques and analytics for cloud security - Chakraborty, Rajdeep; Ghosh, Anupam; Mandal, Jyotsna Kumar, 1960- (Hoboken, NJ : Wiley ; Beverly, MA : Scrivener Publishing, 2022)
This book covers new methods, surveys, case studies, and policy with almost all machine learning techniques and analytics for cloud security solutions. The aim of Machine Learning Techniques and Analytics for Cloud Security is to integrate machine learning approaches to meet various analytical issues in cloud security. Cloud security with ML has long-standing challenges that require methodological and theoretical handling. The conventional cryptography approach is less applied in resource-constrained devices. To solve these issues, the machine learning approach may be effectively used in providing security to the vast growing cloud environment. Machine learning algorithms can also be used to meet various cloud security issues, such as effective intrusion detection systems, zero-knowledge authentication systems, measures for passive attacks, protocols design, privacy system designs, applications, and many more. The book also contains case studies/projects outlining how to implement various security features using machine learning algorithms and analytics on existing cloud-based products in public, private and hybrid cloud respectively.
Conceptual Aspects on Cloud and Applications of Machine Learning. Hybrid Cloud: A New Paradigm in Cloud Computing / Moumita Deb, Abantika Choudhury -- Recognition of Differentially Expressed Glycan Structure of H1N1 Virus Using Unsupervised Learning Framework / Shillpi Mishrra -- Selection of Certain Cancer Mediating Genes Using a Hybrid Model Logistic Regression Supported by Principal Component Analysis (PC-LR) / Subir Hazra, Alia Nikhat Khurshid, Akriti -- Cloud Security Systems Using Machine Learning Techniques. Cost-Effective Voice-Controlled Real-Time Smart Informative Interface Design With Google Assistance Technology / Soumen Santra, Partha Mukherjee, Arpan Deyasi -- Symmetric Key and Artificial Neural Network With Mealy Machine: A Neoteric Model of Cryptosystem for Cloud Security / Anirban Bhowmik, Sunil Karforma, Joydeep Dey -- An Efficient Intrusion Detection System on Various Datasets Using Machine Learning Techniques / Debraj Chatterjee -- You Are Known by Your Mood: A Text-Based Sentiment Analysis for Cloud Security / Abhijit Roy, Parthajit Roy -- The State-of-the-Art in Zero-Knowledge Authentication Proof for Cloud / Priyanka Ghosh -- A Robust Approach for Effective Spam Detection Using Supervised Learning Techniques / Amartya Chakraborty, Suvendu Chattaraj, Sangita Karmakar, Shillpi Mishrra -- An Intelligent System for Securing Network From Intrusion Detection and Prevention of Phishing Attack Using Machine Learning Approaches / Sumit Banik, Sagar Banik, Anupam Mukherjee -- Cloud Security Analysis Using Machine Learning Techniques. Cloud Security Using Honeypot Network and Blockchain: A Review / Smarta Sangui, Swarup Kr Ghosh -- Machine Learning-Based Security in Cloud Database-A Survey / Utsav Vora, Jayleena Mahato, Hrishav Dasgupta, Anand Kumar, Swarup Kr Ghosh -- Machine Learning Adversarial Attacks: A Survey Beyond / Chandni Magoo, Puneet Garg -- Protocols for Cloud Security / Weijing You, Bo Chen -- Case Studies Focused on Cloud Security. A Study on Google Cloud Platform (GCP) and Its Security / Agniswar Roy, Abhik Banerjee, Navneet Bhardwaj -- Case Study of Azure and Azure Security Practices / Navneet Bhardwaj, Abhik Banerjee, Agniswar Roy -- Nutanix Hybrid Cloud From Security Perspective / Abhik Banerjee, Agniswar Roy, Amar Kalvikatte, Navneet Bhardwaj -- Policy Aspects. A Data Science Approach Based on User Interactions to Generate Access Control Policies for Large Collections of Documents / Jedidiah Yanez-Sierra, Arturo Diaz-Perez, Victor Sosa-Sosa -- AI, ML, & Robotics in iSchools: An Academic Analysis for an Intelligent Societal Systems / P K Paul.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed December 13, 2021).
John Wiley and Sons
Keywords: Machine learning; Cloud computing -- Security measures; Apprentissage automatique; Infonuagique -- x; Machine learning